El diagnóstico médico legal ante la presencia de un himen complaciente en delitos de violencia sexual - Angulo Mujica, Gladys Jessenia (Machala : Universidad Técnica de Machala, 2022)
Introduction: Crimes against sexual violence constitute the most important emerging social pathology in cases of abuse against women. The present investigation aims to determine the impact of the legal medical diagnosis in the presence of the hymen that complies with the gynecological examination presented by the affected groups. moment of the medico-legal assessment of an alleged violation. Objective: Identify the legal medical diagnosis in the presence of the hymen that complies with the gynecological examination presented by the affected groups at the time of the legal medical assessment of alleged rape. Materials and Methods: Descriptive, retrospective study obtained in databases such as Scielo, PubMed, Google Scholar, and Cochrane, of the last 5 years and that contribute to the proposed theme. Results: 23 studies were included, of which 10 belong to journals postulated for the third quartile of scientific evidence where the legal medical diagnosis was analyzed in the presence of a compliant hymen in crimes of sexual violence. Conclusions: The expertise that concludes the presence of a compliant hymen is not enough to conclude that there was or was not consent by the victim. A joint assessment of the entire amount of evidence must be carried out, the legal medical certificate that determines a compliant hymen does not rule out the crime of rape, since there are legal medical and psychological certificates that certify the physical signs in other parts of the body and the sequels in the personality of the victim due to the facts.
Introducción: Los delitos contra la violencia sexual constituyen la patología social emergente más importante de los casos de abuso contra la mujer, la presente investigación tiene por objetivo determinar el impacto del diagnóstico médico legal ante la presencia del himen complaciente al examen ginecológico que presentan los grupos afectados al momento de la valoración médico legal de una supuesta violación. Objetivo: Analizar el diagnóstico médico legal ante la presencia del himen complaciente al examen ginecológico que presentan los grupos afectados al momento de la valoración médico legal de una supuesta violación sexual. Materiales y Métodos: Estudio descriptivo, retrospectivo obtenido en bases de datos como: Scielo, PubMed, Google Académico y Cochrane, de los últimos 5 años y que aportan con la temática propuesta. Resultados: Se incluyeron 23 estudios de los cuales 10 pertenecen a revistas postuladas de tercer cuartil de evidencia científica donde se analizó el diagnóstico médico legal ante la presencia de un himen complaciente en delitos de violencia sexual Conclusión: La pericia que concluye la presencia de himen complaciente no es suficiente para concluir que existió o no consentimiento por la víctima. Se deberá realizar una valoración conjunta de todo el caudal probatorio, el certificado médico legal que determine un himen complaciente, no descarta el delito de violación sexual, pues se tienen los certificados médico legal y psicológico que acreditan los signos físicos en otras partes del cuerpo y las secuelas en la personalidad de la víctima debido a los hechos.
Keywords: VIOLACION; DELITO SEXUAL; HIMEN; MEDICINA LEGAL